Cloud structure and composition of Jupiter's atmosphere - Irwin, P (1999)
The understanding of the composition and cloud structure has advanced greatly in the last few years and in particular was greatly improved upon following the highly successful Pioneer and Voyager missions to that planet. Recently the Galileo spacecraft has gone into orbit about Jupiter and its remote sensing instruments, including the Near Infrared Mapping Spectrometer (NIMS) and the Solid State Imager (SSI), have yielded exciting new details of the spatial and vertical structure of the Jovian clouds and volatiles. At the same time Galileo's entry probe has made the first ever in situ measurements of conditions in the atmosphere. Recent ground-based observations have also added to the body of evidence from which conditions in the Jovian atmosphere may be inferred. This paper aims to review the current understanding of the composition and cloud structure of Jupiter's atmosphere in the light of the new Galileo results and recent ground-based, and earth-orbiting telescope observations.